2017
DOI: 10.21273/horttech03679-17
|View full text |Cite
|
Sign up to set email alerts
|

Defining Glyphosate and Dicamba Drift Injury to Dry Edible Pea, Dry Edible Bean, and Potato

Abstract: Field trials using sublethal doses of glyphosate, dicamba, or mixtures of both herbicides on dry edible pea (Pisum sativum), dry edible bean (Phaseolus vulgaris), and potato (Solanum tuberosum) were conducted at six locations to determine the injury potential if spray drift were to occur. All studies used three increasing sublethal doses of glyphosate and dicamba, which were labeled as low, medium, and high. The doses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 11 publications
3
20
0
1
Order By: Relevance
“…Soil at Inkster was an Inkster coarse-loamy, mixed, superactive, frigid Pachic Hapludolls (15% clay, 66% sand, 19% silt) (USDA-NRCS 2017). Studies were conducted from 2015 to 2016 and from 2016 to 2017 (Hatterman-Valenti et al 2017). In the first year of each experiment, mother plants (experimental generation 1) were treated at tuber initiation to simulate the latest timing dicamba and glyphosate would be applied for weed control in soybean.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil at Inkster was an Inkster coarse-loamy, mixed, superactive, frigid Pachic Hapludolls (15% clay, 66% sand, 19% silt) (USDA-NRCS 2017). Studies were conducted from 2015 to 2016 and from 2016 to 2017 (Hatterman-Valenti et al 2017). In the first year of each experiment, mother plants (experimental generation 1) were treated at tuber initiation to simulate the latest timing dicamba and glyphosate would be applied for weed control in soybean.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have reported the effects of glyphosate on potato when treated during the growing season (Colquhoun et al 2017; Hatterman-Valenti 2014; Hatterman-Valenti et al 2017; Hutchinson et al 2014; Wall 1994; Worthington 1985). Worthington (1985) reported that glyphosate treatments applied to a growing crop of potatoes adversely affected the sprout growth of the harvested tubers planted the following season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that exposure to dicamba and 2,4-D delayed bean maturity and reduced test weight and germination of harvested seed. More recently, Hatterman-Valenti et al (2017) reported that dicamba exposure at flowering (R1) at a rate of 18 g ae ha −1 injured navy and pinto bean up to 53%, delayed maturity, and reduced yield 56% to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…This change will put dry bean at an elevated risk for exposure from dicamba and 2,4-D. Previous research indicated that low doses of these herbicides have the potential to affect dry bean yield and quality (Lyon and Wilson 1986;Hatterman-Valenti et al 2017). However, there are still several questions that remain to be answered regarding modern dry bean varieties and market classes.…”
Section: Introductionmentioning
confidence: 99%